(3cJGH GdaQhbs - (3CHh GdYHGS CMeO Hf CHj GdaVd CSYO Hf LdhGf GdWHjH, GHf LdhGfs
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi CeG HYO aEfi eG QCjJ CWHGA GdReGf dG jYQahf ef GdCeQGV EdG eG JUhQhg Yf GdcJH s
(3BNQgG (B:s
(3hPdc Cf GdRjJhf Ef cGf CHjV agh Odjd GdPHhd hEf cGf CMeQ agh Odjd GdCNJQGb Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs